Potential Test of Lactic Acid Bacteria Isolates from Palm Sap (Borassus flabellifer L.) as Antimicrobial against Salmonella typhi - Falakh, Muhammad Fajrul; Tri Asri, Mahanani (LenteraBio : Berkala Ilmiah Biologi, 2022)
Salmonella typhi is a bacterium that causes typhoid fever in humans. This disease can be treated by using antibiotics. However, continuous use of antibiotics has the potential to cause side effects for the body and trigger bacterial resistance to these antibiotics. Therefore, it is necessary to have another alternative by utilizing Lactic Acid Bacteria (LAB) as an antimicrobial to inhibit the growth of S. typhi bacteria. This study aims to determine the potential of LAB isolated from palm sap as an antimicrobial in inhibiting the growth of S. typhi bacteria. This research was carried out by preparing the palm sap first, through a 24 hours fermentation process at room temperature and then isolation and characterization of LAB based on macroscopic, microscopic and physiological observations. Furthermore, potential test of LAB from palm sap was carried out on S. typhi bacteria using well method with 3 treatments, namely isolates of LAB of palm sap, negative control (DMSO 10%) and positive control (amoxicillin 10 µg/ml) with 4 repetitions. The result of the isolation from palm sap, obtained 4 isolates that have the potential to inhibit S. typhi bacteria, namely L105A, L105B, L104C and L104D with inhibition values of 8.75±7.25 mm, 6.75±1.70 mm, 5.50±1.29 mm and 5.75±1.70 mm respectively. Thus, LAB isolates obtained from palm sap have the potential to inhibit the growth of S. typhi bacteria.